Nutritional And Health Education Services Under Integrated Child Development Services in An Urban Area of North Karnataka - Jenyz M Mundodan; Chandra S Metgud (Medsci Publications, 2016)
Introduction: Nutritional and Health Education (NHE) activities under Integrated Child Development Services (ICDS) are intended to change behaviour of community in general and specifically of the mothers. Objectives: To assess the utilisation of Nutrition and Health Education services provided under ICDS in urban areas of Belagavi. Methodology: A cross-sectional study was conducted during January to December 2013 among beneficiaries of Anganwadis (AWC) in Urban Areas of Belagavi. There were 912 participants who included Mothers of Children aged less than 6 years, Pregnant and Lactating Women, Adolescent Girls and Non-Pregnant Non-Lactating Women enrolled at the AWC. A predesigned questionnaire was used to collect data regarding utilisation of Nutrition and Health Education services provided through the AWC. Results: Of the 912 respondents, 585 had attended at least one session of NHE. The topics commonly discussed were Family Planning, Balanced Diet and Hygiene and Sanitation. Just over half the respondents said that the NHE activity resulted in some change in their practices. The common reason given for not attending the sessions was the unsuitable timing. Conclusions: Overall there is a room for improvement in the NHE activities provided under ICDS.